Peripheral compound odontoma erupting in the gingiva - Hanemann, João AC (BioMed Central, 2013)
BACKGROUND: Peripheral odontoma arising in the extraosseous soft tissues is rare and if not removed early, may enlarge over time and eventually erupt in the oral cavity. CASE PRESENTATION: A 15-year-old girl presented with “denticles on the gingiva”. During the intraoral examination, seven small tooth-like structures were found. These were exposed in the anterior left gingiva between the permanent maxillary lateral incisor and canine teeth, and the left first premolar was absent. Radiographic examination revealed irregular tooth-like structures without evidence of bone involvement. CONCLUSION: The lesion was surgically removed, and the specimens were analyzed histopathologically. The diagnosis of compound odontoma was established. CLINICAL SIGNIFICANCE: This is the twelfth reported case of peripheral odontoma in the gingiva and the first one that erupted in the oral cavity.